PENGARUH PENGETAHUAN PRODUK, BIAYA ADMINISTRASI DAN BAGI HASIL TERHADAP MINAT MASYARAKAT - Ach Rosidi (Jurnal Ilmu Ekonomi, 2021)
The purpose of this research is to examine and analyze the effect of product knowledge, administrative costs and profit sharing on public interest. The population is customers at the savings account of KCP Sampang with a sample of 100 respondents and using incidental sampling techniques, primary data collection using questionnaires and secondary data using literature and documentation studies. Hypothesis testing in this study using multiple linear regression. Simultaneously product knowledge, administrative costs and profit-sharing have a significant effect on people's interest in becoming customers in KCP Sampang's barokah savings. Partially, product knowledge has a positive effect on customer interest, administrative costs have the most dominant effect on public interest and profit sharing has an effect on customer interest.